2011
DOI: 10.1007/s11483-011-9214-3
|View full text |Cite
|
Sign up to set email alerts
|

Haishengsu, a Protein from Shellfish Tegillarca L. granosa, Inhibits the Growth and the Activity of Matrix Metalloproteinases-2 and -9 in Human Lung Carcinoma

Abstract: Haishengsu (HSS) is a seashell protein extracted from Tegillarca L. granosa, a type of Malaysian shellfish. Previous in vitro studies showed that HSS might possess biological anticancer activity. In this combined in vitro and in vivo study, we investigated the inhibitory effects of HSS on tumor growth, invasion, and metastasis using human lung carcinoma cell lines A549 and NCI-H292, both intensely positive for matrix metalloproteinases-2 (MMP-2) and MMP-9. HSS significantly inhibited the proliferation of A549 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…HSS has a potential cytotoxic effect on human ovarian cancer cells (SKOV-3 and OVCAR-3), which was mediated by multiple signal molecules including bcl-2, caspase-3, b-catenin, and CD24 [17]. HSS possesses a capacity to inhibit the growth of human lung carcinoma cells (A549 and NCI-H292) by suppressing the activities and expressions of MMP-2 and MMP-9 [21]. The growths of transplanted K562 and K562/ADM tumors were inhibited in the presence of HSS in mice [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSS has a potential cytotoxic effect on human ovarian cancer cells (SKOV-3 and OVCAR-3), which was mediated by multiple signal molecules including bcl-2, caspase-3, b-catenin, and CD24 [17]. HSS possesses a capacity to inhibit the growth of human lung carcinoma cells (A549 and NCI-H292) by suppressing the activities and expressions of MMP-2 and MMP-9 [21]. The growths of transplanted K562 and K562/ADM tumors were inhibited in the presence of HSS in mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…Haishengsu (HSS) is an extract isolated from T. granosa, and its major chemical constituents are proteins with a molecular weight ranging from 15 to 23 kDa. Our previous experimental result indicated that HSS displayed substantial potential inhibitory effects on several types of cancer cell lines including human ovarian cancer cells SKOV-3 and OVCAR-3 [17], human leukemic cells K562 and K562/A02 [18][19][20], and human lung carcinoma cells A549 and NCI-H292 [21]. The aim of the present research was to study the apoptosisinducing activity of HSS in human hepatocellular carcinoma BEL-7402 cells and investigate the underlying mechanism.…”
Section: Introductionmentioning
confidence: 94%
“…It is rich in n‐3 polyunsaturated fatty acid (28.7–37.0% of total fatty acids) and contains predominantly high contents of DHA and EPA (7.9‐17.4%) (Nguyen et al , ). Its protein also contains substances that can prevent tumours (Liu et al , ; Chi et al , ). Furthermore, it is rich in blood, which is different from many other types of shellfish.…”
Section: Introductionmentioning
confidence: 99%
“…T. granosa has been well researched in the field of genetics, which includes cDNA cloning and gene expression, as well as the functional study on the immune expression of hemoglobin gene [12]. In recent years, it has been reported that T. granosa extracts contained several active protein components [13], with diverse activities against fatigue [14], coagulation [15] and tumor growth [16,17]. Despite these findings, the purified protein with antitumor activity from T. granosa has not been reported.…”
Section: Introductionmentioning
confidence: 99%